Tuberculosis and COVID-19 co-infection in Serbia: Pandemic challenge in a low-burden country - Adzic-Vukicevic, Tatjana; Stosic, Maja; Antonijevic, Gordana; Jevtic, Miroslav; Radovanovic-Spurnic, Aleksandra; Velickovic, Jelena (Frontiers in Medicine, 2022)
Introduction: COVID-19 and tuberculosis (TB) represent global threats for public health system. The impact of COVID-19 on TB results in reduction of the number of notified TB cases, delayed diagnosis and treatment, and increased case fatality and mortality rates. The aim of the study was to analyze TB/COVID-19 co-infected cohort in Serbia as a low burden country and compare to the Global TB/COVID-19 cohort. Methods: Retrospective analysis of 53 TB and COVID-19 co-infected patients treated in COVID hospital „Batajnica“in Belgrade and Special Hospital for Pulmonary Diseases „Ozren“ Sokobanja in the period from 6th of March 2020 to 1st of April 2022 was performed and comparative analysis with the Global cohort published recently. Results: TB/COVID-19 cohort in Serbia composed of significantly less migrants and diabetes cases, while more cases with chronic respiratory diseases compared to global. Descriptive analysis of TB cases in Serbian TB/COVID-19 cohort showed less cases diagnosed with sputum smear and Gene Xpert/HAIN, less EPTB and mono resistant cases, while more cases diagnosed with solid culture, more cases with unilateral pulmonary infiltrate (with bilateral cavity lessons) and bilateral pulmonary infiltrate (no cavities) compared to TB/COVID-19 cases worldwide. Nasal congestion and fever was more common COVID -19 symptom in global cohort. Radiology at diagnosis of COVID-19 was more commonly used in Serbia. Typical bilateral ground opacities were less common among Serbian patients, Serbian patients spent fewer days in hospital, achieved higher PCR conversion rate and TB treatment success rate. Conclusions: Serbian TB/COVID-19 cohort achieved higher treatment success rate compared to global cohort. Encouraging vaccination against SARS-CoV-2 for people with a current or past TB disease, as well as rapid diagnosis and targeted treatment of TB in highly specialized pulmonology institutions, present key points to avoid excessive morbidity and mortality.